Tafakkur Filosofis-Analogis Sepak Bola dalam Terminologi Religius dan Sains - Robingun Suyud El Syam; Akhmad Khoiri (Student Research Journal, 2023)
Football is a popular sport worldwide. From small children, teenagers, adults to the elderly, all are fond of this sport. Of course it is interesting if football is associated with science and religion. Thus, the aim of this research is to reveal the philosophical-analogical contemplation of football in religious and scientific terminology. With a philosophical-analogical approach, conclude: that football has 11 players, so it is called a team. The number eleven in religious terminology can be related to the obligation of a Muslim which must follow the 5 pillars of Islam and the 6 pillars of faith. With a scientific approach, the number eleven in religious terminology will find a connection with the miracles of Allah SWT and the Prophet Muhammad SAW. The 11 basic football techniques are also a representation of science where it shows the signs of God's greatness. More specific research on the relationship between religion and science regarding football is needed for the sake of depth of essence.